Zakat dan Penanganan Pembiayaan Bermasalah Pada Pelaku Usaha Mikro Kecil dan Menegah (UMKM) - Setyawan, Perdana Nur Ambar (UIN Sunan Kalijaga, 2018)
Abstract: Nowadays, the sharia banking serves as an increasingly vibrant Islamic financial industry with financing as the main sector having the largest contribution in the business operation of sharia banking. Financing for the Micro, Small and Medium Enterprises (MSMEs) functions as one of the considerably profitable components for sharia banks. However, financing small business sectors in Indonesia poses some risks of non-performing financing (NPF), which is of particular concern to regulators. The higher the NPF ratio of a bank, the greater its credit risk. Some of the risks of non-performing financing are unforeseeable circumstances, such as natural disasters, riots and fires, also known as Force Majeure. Using a normative-empirical approach, this study aims to provide an alternative solution to non-performing financing attributed to Force Majeure factors through the appropriate pattern of zakat distribution in favor of debt-ridden MSMEs (gharimin). This alternative solution is not only applicable for reducing the NPF ratio for banks, but also relevant in helping the recovery of debtors’ economic conditions after the occurrence of Force Majeure.Abstrak: Saat ini, sektor perbankan menjadi industri keuangan syari’ah yang kian marak. Sektor bisnis terbesar dari perbankan syari’ah saat ini masih disokong oleh sektor penyaluran pembiayaan. Pembiayaan pada segemen Usaha Mikro Kecil dan Menengah (UMKM) menjadi salah satu komponen laba bagi bank syari’ah yang patut diperhitungkan. Akan tetapi, risiko pembiayaan macet atau Non-Performing Financing (NPF) masih menjadi momok dan hal itu menjadi perhatian khusus bagi regulator. Semakin besar rasio NPF pada suatu bank, semakin tidak sehat juga bank tersebut. Di antara penyebab risiko pembiayaan macet berada di luar kemampuan manusia seperti bencana alam, huru-hara, dan kebakaran atau disebut juga Force Majeure. Dengan menggunakan pendekatan normatif-empiris, penelitian ini menunjukkan bahwa dengan pola pendistribusian zakat yang tepat dan berpihak pada pelaku UMKM yang terlilit hutang (gharimin) maka zakat dapat menjadi solusi alternatif bagi penyelesaian pembiayaan macet yang disebabkan oleh faktor Force Majeure. Tidak hanya dalam mengurangi NPF bagi bank, tetapi juga penanganan pemulihan kondisi ekonomi pada debitur pasca terjadinya Force Majeure.